Understanding Nurse Turnover in Island-Based District Hospitals: Building Strategies for Retention and Workplace Support - Pe, Wella Kristina (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study explored the lived experiences, workplace challenges, and contextual factors influencing nurse turnover at Coron District Hospital, an island-based district hospital in Palawan. Anchored on the Job Demands–Resources Model, Maslow’s Hierarchy of Needs, Benner’s From Novice to Expert Theory, Leininger’s Transcultural Nursing Theory, and Johnson’s Behavioral System Model, the study examined how organizational and contextual conditions shaped nurses’ retention and resignation decisions. A qualitative descriptive research design was employed using semi-structured interviews with ten purposively selected participants, composed of five currently employed nurses and five former nurses who had resigned within the past one to three years. Data were analyzed through thematic analysis. Findings showed that nurses experienced supportive teamwork, camaraderie, and collegial relationships; however, these positive conditions were weakened by resource limitations, inadequate staffing, heavy workload, burnout, delayed salary, insufficient compensation, limited benefits, unclear promotion pathways, leadership inconsistency, transportation and housing concerns, geographic isolation, and family-related obligations. Delayed salary, workload imbalance, career stagnation, and weak organizational support emerged as major reasons for dissatisfaction and resignation. The study concluded that nurse turnover was shaped by cumulative demographic, professional, organizational, and island-based contextual factors rather than a single cause. It recommended timely salary release, improved compensation, staffing reforms, workload redistribution, leadership development, career progression pathways, mentorship, adequate resources, psychosocial support, and context-sensitive assistance such as housing and transportation support. The study aligned with SDG 3, SDG 4, SDG 8, SDG 16, and SDG 17 by addressing healthcare quality, professional development, decent work, institutional governance, and coordinated workforce responses. Its sustainability impact lies in strengthening healthcare workforce stability, service continuity, institutional support, and equitable access to care in geographically isolated healthcare settings.
Keywords: Burnout; Compensation; Coron District Hospital; Island-Based Hospital; Nurse Retention; Nurse Turnover; Staffing Shortage; Thematic Analysis; Workload